FIBER OPTICS INTEGRATION IN PLASTIC WASTE FLOWER CRAFTS FOR COMMUNITY EMPOWERMENT IN POPONGAN VILLAGE: INTEGRASI SERAT OPTIK PADA KERAJINAN BUNGA DARI LIMBAH PLASTIK UNTUK MASYARAKAT DI DESA POPONGAN - Ahmad Marzuki; Ari Handono Ramelan; Agus Supriyanto; Artono Dwijo Sutomo; Devara Ega Fausta; Alvina Adinda Dewi; Alfan Umar Faruq; Choirul Singgih Munandar (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: The community service program conducted by OLE Research Group focuses on processing plastic waste using optical fiber technology to create handicrafts with economic value. The program is carried out in Popongan Village, Karanganyar Regency, and consists of two implementation phases. Objective: This activity aims to educate the community on transforming plastic waste, particularly used water jugs, into ornamental flower crafts enhancing the value through bouquets creation and integration of fiber optic as illuminated ornaments. Method: The program was conducted in two main phases, including outreach and training on making flowers from plastic water, followed by advanced practical in bouquets arrangement and installation of a simple fiber optic system. Program’s success was evaluated using a pre-test and post-test method. Results: The evaluation showed significant improvement in participants performance. Skills in making flowers increased from 30% in 85%. Ability to assemble simple fiber optic-based circuits improved from 0% to 65%, while confidence in participating in group creative activities rose from 40% to 90%. Conclusion: The program effectively enhanced both technical and non-technical skills of participants and supported the transformation of plastic waste into marketable product. Continued mentoring is needed ensure product consistency and strengthen marketing strategies.